2006
DOI: 10.1016/j.phytochem.2005.12.020
|View full text |Cite
|
Sign up to set email alerts
|

PeroxiBase: A class III plant peroxidase database

Abstract: Class III plant peroxidases (EC 1.11.1.7), which are encoded by multigenic families in land plants, are involved in several important physiological and developmental processes. Their varied functions are not yet clearly determined, but their characterization will certainly lead to a better understanding of plant growth, differentiation and interaction with the environment, and hence to many exciting applications. Since there is currently no central database for plant peroxidase sequences and many plant sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 14 publications
1
54
0
6
Order By: Relevance
“…Exhaustive data mining has been performed to detect APRX othologs. Two isoforms with 70-86% identity were identiWed in C. melo and C. sativus (Bakalovic et al 2006). The Cucurbitaceae APRX homologues formed a well supported branch clearly separated from other species peroxidases (Fig.…”
Section: Identiwcation and Analysis Of The Intronic And Promoter Sequmentioning
confidence: 92%
See 1 more Smart Citation
“…Exhaustive data mining has been performed to detect APRX othologs. Two isoforms with 70-86% identity were identiWed in C. melo and C. sativus (Bakalovic et al 2006). The Cucurbitaceae APRX homologues formed a well supported branch clearly separated from other species peroxidases (Fig.…”
Section: Identiwcation and Analysis Of The Intronic And Promoter Sequmentioning
confidence: 92%
“…In previous studies the identiWcation and isolation of an anionic peroxidase (initially named APRX and also named CpPrx01 based on the nomenclature of the Peroxibase, Bakalovic et al 2006) from the apoplast of zucchini was reported. APRX mRNA accumulated strongly in hypocotyls (Carpin et al 1999) particularly in the elongation area (Dunand et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Plant peroxidases belong to the class III of peroxidases and form a large multigenic family with molecular weights varying from 30 up to 150 kDa (Bakalovic et al, 2006;Cosio and Dunand, 2008). Class III peroxidases have variable domain but conserved motifs position in the structures; it is due to the catalytic function preservation, associated always to presence of a heme group with an iron ion interaging with histidine and phenylalanine amino acids residues in conservaed position (Veitch, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The high versatility of isoperoxidases allows them to be involved in a range of physiological and developmental processes (Passardi et al, 2005;Bakalovic et al, 2006). Among these, class III peroxidases (EC 1.11.1.7) can play a role in defence against pathogens by involvement in physiological responses, specific resistance responses, or induction during pathogenesis as a response to damage (Neale et al, 1990;Dowd & Johnson, 2005;Silvar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%